Characterizing and mapping sediment erodibility of Tuttle Creek Lake in northeast Kansas - Bloedel, Penny M. (Kansas State University, 2016)
Tuttle Creek Dam was built in 1962 after near-record flooding in the Kansas River watershed. It has been in operation for over 50 years. In that time, nearly half of its storage capacity has been filled by sediment, reducing its ability to serve its intended purpose under current operations. The Corps of Engineers authorized a study to examine the sediment in Tuttle Creek Lake and determine management strategies to extend its lifespan. This report examines the erodibility of the sediment as a function of depth and distance to dam. Eight sediment cores were tested and analyzed for two erodibility parameters, critical shear stress and erodibility coefficient. After directly comparing these parameters it was determined that Tuttle Creek Lake sediment ranges from erodible to very erodible regardless of depth or location. Analyzing for locational and depth patterns in erodibility coefficients indicated that both influence the erodibility of sediment, with depth being the stronger factor. These results indicate that locations further upstream from the dam and greater depths are the least erodible. Sedimentation patterns were mapped onto a three dimensional model in ArcMap. It is hoped that this research will assist Corps of Engineers leadership in deciding which management practices to pursue for Tuttle Creek Lake.
Keywords: Erosion; Tuttle Creek Lake; Sediment